Management of the Knee Extension Deficit after Acute Trauma - Thiago Alvim do Amaral; David Sadigursky (Case Reports in Orthopedics)
A 25-year-old man initially presented with right knee extension deficit after an acute trauma, caused by a condition known as arthrogenic muscle inhibition. This should not be confused with a mechanical block caused by intra-articular pathology. The loss of knee extension, even if minimal, is disabling and leads to worse results after knee surgical treatment. Therefore, it is necessary to recognize and diagnose arthrogenic muscle inhibition to ensure the best treatment for patients with this condition. In this case report, the patient was managed with a rehabilitation technique resulting in an effective functional gain of the quadriceps and full restoration of knee extension.